Evaluation of age at symptom onset, proband status, and sex as predictors of disease severity in pediatric catecholaminergic polymorphic ventricular tachycardia - Kallas, Dania; Roston, Thomas M; Franciosi, Sonia; Brett, Laura; Lieve, Krystien V V; Kwok, Sit-Yee; Kannankeril, Prince J; Krahn, Andrew D; LaPage, Martin J; Etheridge, Susan; Hill, Allison; Johnsrude, Christopher; et al. (Heart rhythm, 2021)
BACKGROUND: Children with catecholaminergic polymorphic ventricular tachycardia (CPVT) are at risk for sudden death, and a risk stratification tool does not exist. OBJECTIVE: The purpose of this study was to determine whether proband status, age at symptom onset, and/or sex are independent predictors of cardiac events. METHODS: A multicenter, ambispective, cohort of pediatric CPVT patients was categorized by sex, proband status, and age at symptom onset (D1: first decade of life [symptom onset <10 years] or D2: second decade of life [symptom onset 10-18 years, inclusive]). Demographics, therapy, genetics, and outcomes were compared between groups. RESULTS: A total of 133 patients were included and stratified into 58 D1 and 75 D2 patients (68 female and 65 male; 106 probands and 27 relatives). Localization of RYR2 variants to hotspots differed based on proband status and age at symptom onset. The cardiac event rate was 33% (n = 44/133), inclusive of a 3% (n = 4/133) mortality rate, over a median of 6 years (interquartile range 3-11) after time of symptom onset. Proband status, rather than age at of symptom onset or sex, was an independent predictor of time to first cardiac event (P = .008; hazard ratio = 4.4). The 5-, 10- and 15-year event-free survival rates for probands were 77%, 56%, and 46%, respectively, and for relatives were 96%, 91%, and 86%, respectively. Event risk after diagnosis was 48% (32/67) in patients on β-blocker or flecainide alone vs 10% (5/48) in patients on β-blocker plus flecainide and/or left cardiac sympathetic denervation (P <.001). CONCLUSION: Proband status, but not age at symptom onset or male sex, independently predicted an earlier onset of cardiac events. A larger sample size would enable a comprehensive investigation of other risk factors.
Keywords: Catecholaminergic polymorphic ventricular tachycardia; Female; věk při počátku nemoci; dítě; Tachycardia, Ventricular; ženské pohlaví; Kanada; katecholaminergní polymorfní komorová tachykardie; Adolescent; lidé; Polymorphic Catecholaminergic Ventricular Tachycardia; stupeň závažnosti nemoci; Risk Factors; Sex Factors; Canada; Inherited arrhythmia; Spojené státy americké; Male; sexuální faktory; komorová tachykardie; Risk predictors; rizikové faktory; United States; Child; Age of Onset; Pediatrics; mužské pohlaví; Severity of Illness Index; Ryanodine receptor; mladiství; Humans